In Vivo Method to Monitor Changes in HER2 Expression Using Near-Infrared Fluorescence Imaging - Moinuddin Hassan; Victor Chernomordik; Rafal Zielinski; Yasaman Ardeshirpour; Jacek Capala; Amir Gandjbakhche (Molecular Imaging)
Human epidermal growth factor receptor type 2 (HER2) is a well-known biomarker that is overexpressed in many breast carcinomas. HER2 expression level is an important factor to optimize the therapeutic strategy and monitor the treatment. We used albumin binding domain–fused HER2-specific Affibody molecules, labeled with Alexa Fluor750 dye, to characterize HER2 expression in vivo. Near-infrared optical imaging studies were carried out using mice with subcutaneous HER2-positive tumors. Animals were divided into groups of five: no treatment and 12 hours and 1 week after treatment of the tumors with the Hsp90 inhibitor 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17-DMAG). The compartmental ligands–receptor model, describing binding kinetics, was used to evaluate HER2 expression from the time sequence of the fluorescence images after the intravenous probe injection. The normalized rate of accumulation of the specific fluorescent biomarkers, estimated from this time sequence, linearly correlates with the conventional ex vivo enzyme-linked immunosorbent assay (ELISA) readings for the same tumor. Such correspondence makes properly arranged fluorescence imaging an excellent candidate for estimating HER2 overexpression in tumors, complementing ELISA and other ex vivo assays. Application of this method to the fluorescence data from HER2-positive xenografts reveals that the 17-DMAG treatment results in downregulation of HER2. Application of the AngioSense 750 probe confirmed the antiangiogenic effect of 17-DMAG found with Affibody–Alexa Fluor 750 conjugate.